Relationship of socioeconomic status with health behaviors and self‐perceived health in the elderly: A community‐based study, Turkey. Issue 4 (10th October 2013) - Simsek, Hatice; Doganay, Sinem; Budak, Refik; Ucku, Reyhan
Abstract : Aim: The purpose of the present study was to determine the effects of socioeconomic status on health behaviors and perceived health. Methods: The present cross‐sectional study included 2947 community‐dwelling older adults aged 65 years and older. Dependent variables were health behaviors and self‐perceived health. The independent variable was socioeconomic status. Results: In men, the risk of unhealthy diet was higher among the uneducated group (OR 4.48) and among those with poor/very poor economic status (OR 3.31). Additionally, in men, having poor/very poor self‐perceived health was found to be 3.50‐fold significantly higher among the uneducated group than the secondary school and higher‐educated group. Lower education level and lower social class were found to be protective factors for smoking in women. In women, the risk of unhealthy diet was found to be 1.54‐ and 2.18‐fold significantly higher, respectively, among those who graduated from primary school and uneducated. There was also a relationship between poor/very poor economic status and unhealthy diet among elderly women (OR 2.80). In women, the risk of physical inactivity was found to be 1.98‐fold significantly higher in the uneducated group and 1.79‐fold significantly higher in those with poor/very poor economic status, 0.33‐fold significantly lower in skilled employees/white collar workers. With regard to self‐perceived health status, education level and perceived economic status were significantly related to poor/very poor health status in women (OR 2.09 and OR 4.08, respectively). Conclusion: In older men and women, lower socioeconomic status increases the risk of unhealthy diet and poor health perception. In older women, lower socioeconomic status is a protective factor for smoking, but it also increases physical inactivity.Geriatr Gerontol Int 2014; 14: 960–968.